2017
DOI: 10.1080/09515070.2017.1410696
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic distress and effectiveness of psychological treatments delivered at a nationwide student counseling service

Abstract: The aim of this study is to investigate the effectiveness of student counseling in Denmark and to compare the symptomatic distress among student counseling clients with that of Danish outpatients. The pre-intervention level of self-reported symptomatic distress among 1256 students closely paralleled that of psychiatric outpatients. Participants in the intervention study were the 739 student clients with two or more counseling sessions. For the 530 (71.7%) participants with both pre-and post-measurements, the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 55 publications
1
10
0
2
Order By: Relevance
“…The counseling characteristics of the TAU and the PCOMS condition are shown in Table 1, both for individual and group counseling. The counseling in both conditions was short term, focusing on the current problems of the client (Østergård et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The counseling characteristics of the TAU and the PCOMS condition are shown in Table 1, both for individual and group counseling. The counseling in both conditions was short term, focusing on the current problems of the client (Østergård et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…In their annual report, the Center for Collegiate Mental Health (2018) reported a dropout of 32.8% among 19,632 clients; the report included data from 147 student counseling centers, primarily from the United States. A previous study at the Danish Student Counseling Service (Østergård, Fenger, & Hougaard, 2017) found a relatively large proportion of clients with significant deterioration (12.5%), and dropout (31.7%). Thus, for student counseling, there is considerable potential for helping more clients by reducing client dropout and deterioration.…”
mentioning
confidence: 91%
“…Nevertheless, there also exist data from large-scale therapy outcome studies that are consistent with an illusory mental health perspective. Naturalistic outcome studies of therapy, in which self-report data are available for all clients seeking help, typically find that at least 10% of clients record intake scores in the normal range (Østergård et al, 2019;Stiles et al, 2008). Ziem and Hoyer (2019) found that therapist ratings of client symptom severity at intake were higher than ratings made by the clients themselves.…”
Section: The Concept Of Illusory Mental Healthmentioning
confidence: 99%
“…Nello studio di Lee e colleghi (2009), ad esempio, risultava evidente come gli studenti che avevano seguito un percorso di counselling, riportavano migliori risultati accademici e un minor tasso di abbandono degli studi. Il counselling appare, dunque, funzionale ad incentivare il miglioramento delle prestazioni scolastiche degli studenti in difficoltà e le loro prospettive di completamento degli studi (Østergård, Fenger, & Hougaard, 2017).…”
Section: Valeria Biasiunclassified
“…Tra i questionari impiegati alcuni studi (cfr. Strepparava et al, 2015;Østergård et al, 2017) includono il Symptom Check List-90-R (SCL-90-R; Derogatis, 1994).…”
Section: Principali Strumenti Validatiunclassified